A study of the labor process from a technology transformation perspective: the case of internet virtual teams - Meng Liang (SpringerOpen, 2021)
Abstract This article presents an empirical study of the labor process of internet virtual teams. It argues that organizations with a “horizontally virtual and vertically real” structure face a dilemma in the virtual team labor process. While a culture of engineers, which embodies equality, liberty, and cooperation, is the cultural basis of the virtual team, management is bureaucratic, emphasizing individual interests and hierarchical features. The coexistence of the two leads to cooperation and division of labor in virtual teams. Essentially, this is a compromising institutional arrangement adopted by corporations to triangulate technology culture and managerial control to obtain surplus value. Based on the preceding discussion, this paper ends by proposing a new theoretical framework for studying the labor process under the technological conditions of the internet.